THE CONTENT OF 137Cs IN THE ABOVEGROUND PART OF PLANTS IN FRESH PINE WOODS OF UKRAINIAN POLISSIA - Melnyk, V. V. (Scientific Progress & Innovations, 2019)
The radioactive contamination of the aboveground part of plants of pine plantations with 137Cs under the conditions of fresh pine woods of Ukrainian Polissia was investigated. The research was conducted on sample plots established in the Narodychy forestry, where six samples of the aboveground parts of plant species and the corresponding samples of soil were selected. Before measuring 137Cs specific activity all samples were dried to air-dry state and homogenized. The classical method of comparative ecology was taken as a basis of the researches. The average value of soil radioactive contamination within the permanent sample plots varied from 106 to 380 kBq/m2 (the variation coefficient was 29 %). Significant fluctuations of the specific activity values of 137Cs for all the investigated species were found. The maximal content of 137Cs was found in the aboveground part of Melampyrum pretense (104291 Bq/kg) and the minimal one – in Peucedanum oreoselinum (L.) Moench (217 Bq/kg). While comparing the content of 137Cs in the aboveground part of the Poaceae family, it was found that the Koeleria glauca (Spreng.) DC was characterized by considerably higher values of the investigated index than the Festuca ovina L. In the process of analyzing 137Cs concentration in the aboveground part of Vaccinium vitis-idaea L. and Calluna vulgaris (L.) Hill, the fluctuation of the investigated parameter was found within each sample plot. Intensity indices of 137Cs incoming in the aboveground part of plants of fresh pine woods for all the researched species varied considerably: the accumulation coefficient varied from 0.1 to 53.9, the transition coefficient – from 0.8 to 594 m2·kg-1·10-3. According to the results of a single-factor analysis of variance, the aboveground parts of plants were classified into 5 groups as to their ability to accumulate 137Cs. By the accumulation intensity of 137Cs in fresh pine woods plants can be represented in the following order: Melampyrum pratense > Calluna vulgaris (L.) Hill. > Vaccinium vitis-idaea L. > Koeleria glauca (Spreng.) DC > Festuca ovina L. > Peucedanum oreoselinum (L.) Moench. The concentration values of 137Cs in the studied species have a close linear relation with the value of the density of soil radioactive contamination.